Conformational preferences of a polar biaryl: a phase- and enantiomeric purity-dependent molecular hinge. - Clayden, J; Fletcher, S; Rowbottom, S; Helliwell, M (2009)
The favored (R(S)*,M*) diastereoisomer of 2-aryl-pyridine 1 in the solution state results from intramolecular dipole-dipole interactions. In the crystalline state, intermolecular interactions dominate, and the conformation switches reversibly to (R(S)*,P*). Only racemic 1 exhibits this switching property: enantiomerically pure 1 exists as the (R(S)*,M*) diastereoisomer in both the solution and crystalline state.